Study of ancient monuments’ seismic performance based on Passive and Remote Techniques - Kyriakides, Nicholas; Illampas, Rogiros; Lysandrou, Vasiliki; Agapiou, Athos; Masini, Nicola; Sileo, Maria; Catapano, Ilaria; Gennarelli, Gianluca; Lasaponara, Rosa; Soldovieri, Francesco; Hadjimitsis, Diofantos G. (My University, 2018)
“Engineering structures are designed to be safe. The difficulty one trading in this regard is the desire to construct something for a specific purpose out of a material of which one can never know enough in terms of the material’s properties as well as the environment the structure is going to operate in”. Even though this affirmation was initially drawn for modern structures, it however firmly describes the situation of the ancient ones. In the case of ancient monuments, the mechanical properties of the construction materials, their consistency and their homogeneity are highly unknown and can only be determined probabilistically through elaborate testing under legislative and protective to the monuments’ restrictions. On the other hand, the environmental (weather) conditions and natural hazards to which those ancient masonry structures were and still are exposed is even more difficult to be determined with precision and thus monitored, but has certainly led to their degradation. Towards this end, the present study discusses the potentialities of non-destructive passive and remote system investigations of monuments, trying to examine the benefits and drawbacks in relation to the result and in comparison to conventional structural control methods. A selection of the most credible methods for the investigation of monuments is described along with their potential applications. The scope of this investigation is to acquire information regarding the subsurface condition and consequently the structural system of the monument and anticipate its future behavior in destructive earthquake events. This can be achieved through a simulation model, which can be as realistic as the information obtained and can be updated with more thorough information. To demonstrate the application of this updating process in obtaining the response of the monument, a case study tomb “Tomb 4” from the Hellenistic necropolis of the ‘Tombs of the Kings’, in Paphos Cyprus is examined, recapitalizing thus previous work of the team accomplished on the aforementioned monument. The seismic performance of the monument, located in a moderate earthquake hazard area, will be examined based on passive and remote data acquisition and simulation results will be shown.
Keywords: Structural survey; Underground monument; Cultural heritage; Passive and remote techniques; Seismic analysis